FEMININITY IN MEN AND SOCIAL EXCLUSION - Parveen, Kaur; Arif, Jawaid; Eshvin, Raj Singh; Khoo, Wei Yang; Lim, Zi Ying; Yap, Sui Lin; Mohd Harith, Heykal; Nazir, Hussain Shah; Ramzuan, Bolhassan (2020)
Social exclusion of femininemen is an issue often over looked where these men face struggles and backlash for being feminine. The purpose of this study is to examine the correlation between femininity in men and social exclusion within social, economic, and familial dimensions. This study employed a quantitative method among 122 Malaysian men. Measurements are made with a 29 Likert-type item self-conducted online questionnaire which includes the Bem Sex-Role Inventory (BSRI) as a measurement of femininity in men. The findings demonstrate a minor correlation between femininity in men and social exclusion in the economic and social dimensions. Furthermore, a negative association is shown between femininity and exclusion in the familial or affective dimension.